TOP2A inhibition and its cellular effects related to cell cycle checkpoint adaptation pathway - Maria C. Arroyo López; M. A. Fernández-Mimbrera; E. Gollini; A. Esteve-Codina; A. Sánchez; Juan Alberto Marchal Ortega (Scientific Reports)
Abstract In this study, we investigate the G2 checkpoint activated by chromosome entanglements, the so-called Decatenation Checkpoint (DC), which can be activated by TOP2A catalytic inhibition. Specifically, we focus on the spontaneous ability of cells to bypass or override this checkpoint, referred to as checkpoint adaptation. Some factors involved in adapting to this checkpoint are p53 and MCPH1. Using cellular models depleted of p53 or both p53 and MCPH1 in hTERT-RPE1 cells, we analyzed cell cycle dynamics and adaptation, segregation defects, apoptosis rate, and transcriptional changes related to prolonged exposure to TOP2A inhibitors. Our findings reveal that cell cycle dynamics are altered in MCPH1-depleted cells compared to control cells. We found that MCPH1 depletion can restore the robustness of the DC in a p53-negative background. Furthermore, this research highlights the differential effects of TOP2A poisons and catalytic inhibitors on cellular outcomes and transcriptional profiles. By examining the different mechanisms of TOP2A inhibition and their impact on cellular processes, this study contributes to a deeper understanding of the regulation and physiological implications of the DC and checkpoint adaptation in non-carcinogenic cell lines.